Photocatalytic granular material and preparation method therefor

JP2025504707AActive Publication Date: 2025-02-17KOREA INST OF CIVIL ENG & BUILDING TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024538678
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-12-22
Filing Date
2022-12-22
Publication Date
2025-02-17
Estimated Expiration
2042-12-22

Smart Images

  • Figure 2025504707000001_ABST
    Figure 2025504707000001_ABST
Patent Text Reader

Abstract

A photocatalyst modification method, a photocatalyst granular material containing photocatalyst crystals modified thereby, and a preparation method therefor are disclosed, the photocatalyst modification method comprising: hydrothermally synthesizing the photocatalyst by reacting the photocatalyst with an alkaline solution at a temperature of at least 100°C or higher to separate a monoatomic layer of the photocatalyst; and treating the hydrothermally synthesized photocatalyst so that the photocatalyst crystals have a tubular shape.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] FIELD OF THE DISCLOSURE The present disclosure relates to a photocatalytic granular material capable of performing at least one of organic matter decomposition, bacteria removal, and virus removal, and a method for preparing the same.

[0002] This research was supported by research grants from the "Photocatalytic modification technology and air conditioning filter development" project of the 2021 KICT (Korea Institute of Construction Technology) Major Program (Project No.: 20210218-001, Research Project Name: Corporate Support and Performance Expansion of Construction Industry Innovation, Contribution Rate: 1 / 2) and the "Development of an emergency modular system for viral disaster response - Development of modular equipment and isolation systems that can prevent the spread of infectious diseases and enable rapid response" project of the 2022 KICT Major Program (Project No.: 20220238-001, Research Project Name: Safety, Security, and Ground Transportation Technology Development, Contribution Rate: 1 / 2). [Background technology]

[0003] A large-scale outbreak of new / mutated viruses could pose a threat to people's lives and safety and cause serious damage to the national economy.

[0004] We have been continuously and repeatedly experiencing shock and fear due to the arrival of new high-risk respiratory infectious diseases in the country in the 2000s, including SARS in 2003, Swine Flu in 2009, MERS in 2015, and COVID-19 in 2020. These respiratory infectious diseases are characterized by their spread when infectious agents (pathogenic viruses or bacteria) exhaled by infected individuals through coughing or other means enter the airways of uninfected individuals. In fact, there are frequent cases where the air in indoor living environments is contaminated by infectious agents, causing serious spread of infectious diseases. In addition, even in terms of economic losses, the scale of social and economic losses caused by MERS in 2015 was reported to be 10,844.8 billion Korean won, and the scale of losses from COVID-19 in particular is expected to be astronomical.

[0005] For this reason, interest in and the need for effective home isolation techniques to respond to infectious diseases and create safe and secure living environments are currently growing internationally. In fact, it is extremely important to control contamination of infectious pathogens to suppress the spread of infectious diseases and minimize losses in immigration facilities, which are the entry point for infectious diseases from overseas, hospital facilities where patients with infectious diseases gather, elderly and nursing homes where people who are susceptible to infectious diseases live, educational facilities and daycare centers where young children and teenagers live together, and public facilities and public transportation where an unspecified number of people frequently enter and use.

[0006] In order to create a safe and secure living environment that minimizes the risk of the spread of high-risk respiratory infections, there is a need for home isolation technology that can effectively remove airborne pathogens. In particular, there is an increasing need to develop air purification devices (air purifiers, air sterilizers, purification and ventilation devices) with antiviral or antibacterial properties that can constantly, quickly, and directly remove airborne pathogens in order to minimize the risk of airborne infections in enclosed spaces where adequate ventilation is difficult due to fine dust problems, heating and cooling problems, etc., or where ventilation is impossible due to the special nature of the spatial structure and use. Summary of the Invention [Problem to be solved by the invention]

[0007] The present disclosure is intended to solve the problems of the related art described above, and one aspect of the present disclosure is to provide a photocatalytic granular material having improved photocatalytic activity and increased adsorption capacity compared to the related art, and exhibiting purification, antiviral, and antibacterial functions that enable decomposition and / or oxidation of organic matter and / or organisms, thereby eliminating harmful substances (fine dust precursors or volatile organic compounds) and harmful microorganisms (viruses or bacteria), and a method for preparing the same.

[0008] However, the technical problem solved in the embodiments of the present disclosure is not limited to the problem to be solved, and there may be other problems to be solved. [Means for solving the problem]

[0009] As a technical means for achieving the above technical problem, a photocatalyst modification method according to one embodiment of the present disclosure may include the steps of: performing hydrothermal synthesis to react the photocatalyst with an alkaline solution at a temperature of 100°C or higher, so as to separate a monoatomic layer of the photocatalyst; and treating the hydrothermally synthesized photocatalyst so that the crystals of the photocatalyst have a tubular shape.

[0010] A photocatalyst according to an embodiment of the present disclosure may include a plurality of photocatalytic crystals modified by a photocatalyst modification method according to an embodiment of the present disclosure.

[0011] The photocatalytic granular material according to one aspect of the present disclosure may include a photocatalyst according to one aspect of the present disclosure.

[0012] A method for preparing a photocatalytic granular material according to one embodiment of the present disclosure may include the steps of: preparing a modified photocatalyst by a photocatalytic modification method according to one embodiment of the present disclosure; producing a photocatalytic paste by mixing the modified photocatalyst with distilled water; forming the photocatalytic paste into granules (granular material); and drying the formed granules to form photocatalytic granules.

[0013] A method for preparing a photocatalytic granular material according to another embodiment of the present disclosure may include: preparing a modified photocatalyst by a photocatalytic modification method according to one embodiment of the present disclosure; producing a photocatalytic paste by mixing the modified photocatalyst with distilled water and further mixing an open-cell type circular foam made of a material having a melting point lower than that of the modified photocatalyst or a piece of thread made of a material having a melting point lower than that of the photocatalyst; forming the photocatalytic paste into granules; and drying the formed granules to form photocatalytic granules.

[0014] A method for preparing a photocatalytic granular material according to yet another aspect of the present disclosure may include: coating granules with a liquid photocatalyst; and drying the granules coated with the liquid photocatalyst to form photocatalytic granules, where coating the granules with the liquid photocatalyst may be by immersing the granules in the liquid photocatalyst or spraying the liquid photocatalyst onto the granules.

[0015] The solutions to the problems are merely exemplary and should not be construed as intended to limit the present disclosure. In addition to the embodiments described above, there may be additional embodiments in the drawings and detailed description of the present disclosure. [Advantageous Effects]

[0016] According to an embodiment of the solution to the problem described above, compared with the related art, a photocatalytic granular material can be implemented, which can improve the performance of photocatalytic activity, increase the adsorption capacity, increase the organic matter removal effect by enabling the decomposition and / or oxidation of organic matter and / or organisms, and exhibit purification, antiviral, and antibacterial functions by inactivating and / or removing harmful microorganisms (viruses or bacteria), thereby simplifying the preparation process. [Brief description of the drawings]

[0017] [Figure 1] FIG. 1 is a conceptual diagram illustrating a photocatalytic reforming method according to one embodiment of the present disclosure.

[0018] [Diagram 2] 1 is a SEM photograph of a photocatalyst (photocatalyst powder) before (unmodified) modification by a photocatalyst modification method according to one embodiment of the present disclosure.

[0019] [Diagram 3] 1 is a SEM photograph of Ti (Li-Ti) modified by using Li according to a photocatalytic modification method according to one embodiment of the present disclosure.

[0020] [Figure 4] 1 is a SEM photograph of Ti modified by using Na (Na-Ti) according to a photocatalytic modification method according to one embodiment of the present disclosure.

[0021] [Diagram 5] 1 is a SEM photograph of Ti modified by using K (K-Ti) according to a photocatalytic modification method according to one embodiment of the present disclosure.

[0022] [Figure 6A] 1 is a table showing the results of measurements of the surface area of ​​a photocatalyst before and after modification according to one embodiment of the photocatalytic modification method of the present disclosure.

[0023] [Figure 6B]1 is a table showing the results of elemental analysis of a photocatalyst before and after modification according to one embodiment of the photocatalytic modification method of the present disclosure.

[0024] [Figure 7A] 1 is a graph showing the XRD pattern analysis results of three kinds of photocatalysts Li-Ti, Na-Ti, and K-Ti modified by Li, Na, and K, respectively, after drying according to a photocatalytic modification method according to an embodiment of the present disclosure;

[0025] [Figure 7B] FIG. 1 is a graph showing the analysis results of XRD patterns after calcination of three kinds of photocatalysts Li-Ti, Na-Ti, and K-Ti modified by Li, Na, and K, respectively, according to a photocatalytic modification method according to an embodiment of the present disclosure.

[0026] [Figure 8] FIG. 1 is a graph showing the results of evaluating the activity after calcination of three types of photocatalysts Li-Ti, Na-Ti, and K-Ti, which were modified with Li, Na, and K, respectively, according to a photocatalytic modification method according to an embodiment of the present disclosure.

[0027] [Figure 9] 1 is a table summarizing the results of evaluating three photocatalysts Li-Ti, Na-Ti, and K-Ti modified with Li, Na, and K, respectively, according to a photocatalytic modification method according to an embodiment of the present disclosure.

[0028] [Figure 10] 1 is a graph showing the results of evaluating the organic matter removal performance of a photocatalyst calcined with MTA powder after chemical treatment according to one embodiment of the photocatalytic modification method of the present disclosure (showing the results of photocatalytic activity evaluation for each treatment temperature).

[0029] [Figure 11] 1 is a graph showing the XRD diffraction analysis results of a photocatalyst calcined with MTA powder at a temperature of 550° C. after chemical treatment according to an embodiment of the photocatalytic modification method of the present disclosure.

[0030] [Figure 12] 1 is a graph showing particle size distribution data for the primary grinding of a photocatalytic modification method according to one embodiment of the present disclosure.

[0031] [Figure 13] 1 is a graph showing particle size distribution data for secondary grinding / sorting of a photocatalytic modification process according to one embodiment of the present disclosure.

[0032] [Figure 14] 1 is a schematic flow chart illustrating a method for preparing a photocatalytic granular material according to a first embodiment of the present disclosure.

[0033] [Figure 15] 1 is a table listing heating conditions according to drying oven types in the case of a continuous drying oven in step S700 of the method for preparing a photocatalytic granular material according to the first embodiment of the present disclosure.

[0034] [Figure 16] 1 is a table listing heating conditions according to the type of drying oven in case of a non-continuous drying oven in step S700 of the method for preparing a photocatalytic granular material according to the first embodiment of the present disclosure.

[0035] [Figure 17A] 1 is a schematic flow chart illustrating a method for preparing a photocatalytic granular material according to a second embodiment of the present disclosure, in which a photocatalytic paste is produced by mixing a photocatalyst with distilled water and an open-cell type circular foam.

[0036] [Figure 17B] 1 is a schematic flow chart illustrating a method for preparing a photocatalytic granular material according to a second embodiment of the present disclosure, in which a photocatalytic paste is produced by mixing a photocatalyst with distilled water and pieces of thread.

[0037] [Figure 18]FIG. 10 is an exemplary diagram of an open-cell type foam of the method for preparing a photocatalytic granular material according to the second embodiment of the present disclosure.

[0038] [Figure 19] 11 is a table listing heating conditions according to drying oven type in the case of a continuous drying oven in step S700 of the method for preparing a photocatalytic granular material according to the second embodiment of the present disclosure.

[0039] [Figure 20] 11 is a table listing heating conditions according to drying oven type in case of a non-continuous drying oven in step S700 of the method for preparing a photocatalytic granular material according to the second embodiment of the present disclosure.

[0040] [Figure 21] 4 is a schematic flow chart illustrating a method for preparing a photocatalytic granular material according to a third embodiment of the present disclosure.

[0041] [Figure 22] 11 is a table listing heating conditions according to drying oven type for a continuous drying oven in step S300 of the method for preparing photocatalytic granular material according to the third embodiment of the present disclosure.

[0042] [Diagram 23] 11 is a table listing heating conditions according to the drying oven type in the case of a discontinuous drying oven in step S300 of the method for preparing a photocatalytic granular material according to the third embodiment of the present disclosure.

[0043] [Figure 24] 1 is a graph showing the results of evaluation of the bacteria and virus removal performance of a photocatalyst before modification. [Diagram 25] 1 is a graph showing the results of evaluation of the bacteria and virus removal performance of a photocatalyst before modification. [Figure 26] 1 is a graph showing the results of evaluation of the bacteria and virus removal performance of a photocatalyst before modification.

[0044] [Figure 27] 1 is a graph showing the results of evaluating the virus removal performance of each of the modified photocatalysts Li-Ti, Na-Ti, or K-Ti prepared by the photocatalyst modification method according to one embodiment of the present disclosure.

[0045] [Figure 28A] 1 shows the results of evaluating the virus removal performance of photocatalytic granular material according to the first to third embodiments of the present disclosure or photocatalytic granular material prepared by the method for preparing photocatalytic granular material according to the first to fourth embodiments of the present disclosure. [Figure 28B] 1 shows the results of evaluating the virus removal performance of photocatalytic granular material according to the first to third embodiments of the present disclosure or photocatalytic granular material prepared by the method for preparing photocatalytic granular material according to the first to fourth embodiments of the present disclosure. [Figure 29] 1 shows the results of evaluating the virus removal performance of photocatalytic granular material according to the first to third embodiments of the present disclosure or photocatalytic granular material prepared by the method for preparing photocatalytic granular material according to the first to fourth embodiments of the present disclosure. [Figure 30A] 1 shows the results of evaluating the virus removal performance of photocatalytic granular material according to the first to third embodiments of the present disclosure or photocatalytic granular material prepared by the method for preparing photocatalytic granular material according to the first to fourth embodiments of the present disclosure. [Figure 30B] 1 shows the results of evaluating the virus removal performance of photocatalytic granular material according to the first to third embodiments of the present disclosure or photocatalytic granular material prepared by the method for preparing photocatalytic granular material according to the first to fourth embodiments of the present disclosure. [Figure 30C] 1 shows the results of evaluating the virus removal performance of photocatalytic granular material according to the first to third embodiments of the present disclosure or photocatalytic granular material prepared by the method for preparing photocatalytic granular material according to the first to fourth embodiments of the present disclosure.

[0046] [Diagram 31]1 is a graph for explaining the effect of the photocatalyst preparation step of the photocatalyst reforming method according to one embodiment of the present disclosure, specifically, a graph showing the amount of acetaldehyde removed for each firing temperature.

[0047] [Diagram 32] 1 is a graph for explaining the effect of the photocatalyst preparation step of the photocatalyst reforming method according to one embodiment of the present disclosure, specifically, a graph showing the amount of carbon dioxide generated for each firing temperature.

[0048] [Diagram 33] 1 is a graph for explaining the effect of the photocatalyst preparation step of a photocatalyst modification method according to one embodiment of the present disclosure, specifically, a TEM measurement photograph of the prepared photocatalyst powder.

[0049] [Diagram 34] 1 shows the XRD measurement results of the photocatalyst powder prepared in the photocatalyst preparation step of the photocatalyst modification method according to one embodiment of the present disclosure.

[0050] [Diagram 35] 1 shows a SEM / EDX (X1,300) photograph of the photocatalyst powder prepared in the photocatalyst preparation step of the photocatalyst modification method according to one embodiment of the present disclosure.

[0051] [Diagram 36] 1 shows a SEM / EDX (X10,000) photograph of the photocatalyst powder prepared in the photocatalyst preparation step of the photocatalyst modification method according to one embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0052] In the following, in order to facilitate easy implementation by those skilled in the art to which the present disclosure belongs, embodiments of the present disclosure will be described in detail with reference to the accompanying drawings. However, the present disclosure may be implemented in different forms and is not limited to the embodiments described herein. In order to clearly describe the present disclosure in the drawings, parts that are not related to the description are omitted, and similar parts are given the same reference numerals throughout the present disclosure.

[0053] Throughout this specification, when a component is said to be "coupled" to another component, this includes not only when they are "directly coupled" to each other, but also when they are "electrically coupled" to each other with another intervening element therebetween.

[0054] Throughout this specification, when an element is said to be located "on," "above," "on top of," "below," "below" or "at the bottom of" another element, this includes when the element is on top of the other element and in contact with each other, and when there is an intervening element between the two elements.

[0055] Throughout this specification, when a part "comprises" a component, this does not mean to exclude other components, but rather that other components may be further included.

[0056] The present disclosure relates to a photocatalytic granular material and a preparation method therefor.

[0057] In the following, for easy understanding of the present disclosure, a photocatalytic reforming method according to one embodiment of the present disclosure (hereinafter referred to as "the reforming method according to the present disclosure") will be described first.

[0058] The modification method according to the present disclosure includes a step (first step) of performing hydrothermal synthesis in which the photocatalyst is reacted with an alkaline solution at a temperature of at least 100° C. so that a monoatomic layer of the photocatalyst is separated. Additionally, the modification method according to the present disclosure includes a step (second step) of treating the hydrothermally synthesized photocatalyst so that the photocatalyst crystal has a tubular shape. That is, in the modification method according to the present disclosure, the photocatalyst powder and the alkaline solution may be hydrothermally synthesized with each other so that a monoatomic layer is separated, and then the photocatalyst crystal may be transformed into a tubular shape.

[0059] As an example, in the first step, the photocatalyst and the alkaline solution may be mixed and reacted at a temperature of 100°C to 130°C.

[0060] As an example, the alkaline solution may contain at least one of Li, Na, and K.

[0061] Additionally, the photocatalyst may be anatase.

[0062] The photocatalyst may also be titanium oxide or metatitanic acid.

[0063] As described above, referring to FIG. 1, in the reforming method according to the present disclosure, the photocatalyst (e.g., titanium oxide) powder may be reacted in an alkaline solution at high temperature for a long time, and accordingly, the photocatalyst is separated into a monolayer by the alkaline solution. The separated monolayer may take a tubular shape because it is rolled. In this process, a dissolution process may be carried out by the alkaline solution. Impurities contained in the photocatalyst may be removed during the dissolution process, so that only the pure photocatalyst is recovered. In the reforming method according to the present disclosure, the reaction was carried out by adding a common photocatalyst (titanium oxide), mixing it with an alkaline solution, and stirring the mixture. At this time, hydrothermal synthesis may be carried out by maintaining the temperature of the reforming reactor at 130°C.

[0064] Additionally, in the present disclosure, preferably, the alkaline solution may contain at least one of Na and K. Specifically, the alkaline solution may contain at least one of sodium hydroxide (NaOH) and potassium hydroxide (KOH), and in the first stage, the photocatalyst may be dispersed in the alkaline solution by energy equivalent to ultrasonic waves (i.e., dispersed by applying ultrasonic waves), and the photocatalyst may be reacted at a temperature of 100°C to 130°C for 15 to 20 hours to perform hydrothermal synthesis. In addition, in the first stage, after the hydrothermal synthesis, the photocatalyst may be separated into a monoatomic layer by washing with HCl and distilled water by centrifugation.

[0065] Accordingly, for example, the alkaline solution may be sodium hydroxide (NaOH), and in the first step, the photocatalyst may be dispersed in sodium hydroxide by ultrasonic waves, and then hydrothermal synthesis may be carried out to react the photocatalyst at a temperature of 100°C to 130°C for 15 to 20 hours. In addition, in the first step, after the hydrothermal synthesis, the photocatalyst may be separated into a monolayer by washing with HCl and distilled water by centrifugation. Alternatively, the alkaline solution may be potassium hydroxide (KOH), and in the first step, the photocatalyst may be dispersed in potassium hydroxide by ultrasonic waves, and then hydrothermal synthesis may be carried out to react the photocatalyst at a temperature of 100°C to 130°C for 15 to 20 hours. In addition, in the first step, after the hydrothermal synthesis, the photocatalyst may be separated into a monolayer by washing with HCl and distilled water by centrifugation.

[0066] Additionally, the second step may include drying the hydrothermally synthesized photocatalyst.

[0067] Additionally, the second step may include calcining the hydrothermally synthesized photocatalyst.

[0068] In the following, in order to provide a more detailed understanding of the modification method according to the present disclosure, experiments carried out in relation to the modification method according to the present disclosure will be described.

[0069] Experiments were carried out by the aforementioned modification method according to the present disclosure to prepare three kinds of samples Li-Ti, Na-Ti, and K-Ti, in which an alkaline substance was used to pretreat (modify) the photocatalyst (titanium oxide), and the particle shape of each sample was confirmed by SEM. By observing the particle shapes of the photocatalyst (titanium oxide) before modification in FIG. 2 and the modified photocatalyst sample Li-Ti in FIG. 3, it can be seen that the particle composition of the modified sample is more tightly bound than that of the photocatalyst (titanium oxide) before modification. In general, in order to increase the activity and / or adsorption capacity of the photocatalyst performing the surface reaction, the particle size needs to be reduced, or a dense shape needs to be formed to increase the specific surface area. In the case of the Li-Ti sample, it can be seen that the density between particles is improved without a significant change in particle size.

[0070] In addition, it can be seen that the particles of the modified photocatalyst Na-Ti sample in Figure 4 show definite differences from the particles of the photocatalyst (titanium dioxide) before modification: it can be seen that the particles, which were in powder form before modification, have changed to tubular shape and fibrous tissue has formed.

[0071] In addition, referring to FIG. 5, it can be seen that the modified photocatalyst K-Ti sample has very smooth tubular grains, and therefore exhibits the greatest change in grain shape due to the modification.

[0072] In this specification, the purpose of modifying the photocatalyst is to improve the activity and adsorption capacity of the photocatalyst, so a BET analysis was carried out to confirm the change in the photocatalyst before and after modification. Referring to Figure 6A, the specific surface area of ​​the photocatalyst (titanium oxide) before modification was about 59 m 2 / g. However, it can be seen that after modification, the specific surface areas of the three photocatalyst samples Li-Ti, Na-Ti, and K-Ti all increase. In fact, the specific surface area of ​​the modified photocatalyst Li-Ti sample was about 271 m 2 / g (4.6 times the specific surface area of ​​the photocatalyst before modification), and the specific surface area of ​​the Na-Ti sample was approximately 369 m 2 / g (6.2 times the specific surface area of ​​the photocatalyst before modification), and the specific surface area of ​​the K-Ti sample was approximately 426 m 2 It can be seen that the specific surface area of ​​the photocatalyst increases to 1.25 μm / g (7.2 times the specific surface area of ​​the photocatalyst before modification). That is, according to the modification process of the present disclosure, which corresponds to the pretreatment step, it can be determined that the modification process can help improve the activity and / or adsorption capacity of the photocatalyst due to the increase in the specific surface area of ​​the photocatalyst even when the photocatalyst does not exhibit a perfect nano-ring shape.

[0073] In addition, referring to FIG. 6B, according to the results of EXD analysis to determine the elemental composition of the photocatalyst before and after modification, it can be seen that the amount of titanium oxide contained in the photocatalyst before and after modification is about 80 to 90%, which means that the content of impurities is not high; however, considering that carbon is removed during the calcination process to increase the photocatalytic activity (the formation of highly active anatase crystals), the amount of titanium oxide contained in the photocatalyst before modification is 97%, while the amount of titanium oxide contained in each of the three photocatalyst samples Li-Ti, Na-Ti, and K-Ti calcined after modification are all above 99% (up to 99.6%), thereby confirming the effect of the modification in removing impurities.

[0074] In addition, referring to Fig. 7A, the XRD pattern analysis results of drying the three photocatalyst samples Li-Ti, Na-Ti, and K-Ti modified with alkaline materials show that all three photocatalyst samples are in an amorphous crystalline state, and therefore no definite anatase peak appears. In contrast, referring to Fig. 7B, the XRD pattern analysis results of calcining the three photocatalyst samples at a temperature of 600°C show that all three photocatalyst samples have perfect anatase peaks.

[0075] In addition, referring to Figure 8, when evaluating the organic matter removal effect of the three photocatalyst samples modified by using alkaline materials and then calcined, it can be seen that a significant level of organic matter removal performance is achieved in all three photocatalyst samples due to the increase in specific surface area, removal of impurities, and the formation of anatase crystals. In particular, referring to Figure 9, it can be seen that the photocatalytic activity is greatly improved in K-Ti and Na-Ti due to the formation of nano-tubular anatase crystals by the modification and calcination treatment.

[0076] However, although the above process has the advantages of ensuring high purity of the photocatalyst and enhancing the activity and adsorption capacity of the photocatalyst, it has the disadvantages that the treatment process is complicated and many chemicals must be used during the process, which may increase the production cost.

[0077] To compensate for this, the modification method according to the present disclosure was used to modify pre-crystallized metatitanic acid (MTA) rather than the crystallized photocatalyst (titanium oxide).

[0078] Referring to FIG. 10, in terms of the organic matter removal effect of three types of samples obtained by modifying metatitanic acid (MTA) using an alkaline substance and then calcining at different temperatures, it can be seen that the sample calcined at 300°C exhibits activity similar to that of existing photocatalysts (approximately 30% organic matter removal effect), the sample calcined at 550°C exhibits increased photocatalytic activity, and the sample calcined at 600°C exhibits a sharp decrease in photocatalytic activity.

[0079] In general, photocatalytic activity is often observed in the anatase form, and anatase crystals can be obtained by calcining the photocatalyst at temperatures of 500 to 600°C. The temperature at which the anatase form is converted to the rutile form is about 700°C, but when modifying metatitanic acid (MTA), it has been determined that the change to the rutile form occurs at a temperature of 600°C.

[0080] Referring to FIG. 11, it can be seen that an anatase peak appears in the XRD pattern analysis result of the sample confirmed to have the highest photocatalytic activity (organic matter removal effect) (sample calcined at 550° C.).

[0081] It has been confirmed that the particle size of the photocatalyst most easily mixed in the step of producing the photocatalyst paste is approximately 10 μm, and the particle size can be approximated to that by passing through a powdering process in the photocatalyst preparation step. That is, the modification method according to the present disclosure may include a step of preparing a photocatalyst before the above-mentioned first step, and the step of preparing a photocatalyst may include a step of powdering a photocatalyst powder, and although the particle size of the photocatalyst powder is in a fairly wide range, the step of powdering the photocatalyst powder may be performed so that the average particle size of the photocatalyst powder is approximately 10 μm. With reference to FIG. 12, it can be seen that the step of powdering the particles has been processed so that the photocatalyst powder has a particle size distribution of 0.2 to 80 μm and an average particle size of about 8 μm. In addition, in the case of the method for preparing a photocatalyst granular material according to the third embodiment of the present disclosure described later, the step of preparing a liquid photocatalyst may be performed before the step of coating the granules (granular material) with the liquid photocatalyst. The step of powdering the photocatalyst powder may be performed before the step of preparing the liquid photocatalyst.

[0082] In addition, since too small or too large photocatalyst particles can interfere with mixing, the powdered powder may be classified to more precisely control the particle distribution. Referring to Figure 13, it can be seen that the photocatalyst having a particle size distribution of 0.2 to 80 μm and an average particle size of about 8 μm in Figure 12 was classified and processed to have a particle size distribution of 1 to 40 μm and an average particle size of about 10 μm.

[0083] To summarize the contents of the present disclosure based on the experimental results described above, the present disclosure can improve the activity and adsorption capacity by a process of modifying the photocatalyst, i.e., a process of increasing the specific surface area of ​​the photocatalyst (titanium oxide) particles and a process of removing impurities. For this purpose, in the modification method of the present disclosure, the photocatalyst (titanium oxide) powder can be hydrothermally synthesized in a hot alkaline solution to separate into a monoatomic layer, and then dried, so that the highly pure water with the impurities removed forms tubular crystals. In fact, according to the above experimental results, three kinds of samples Li-Ti, Na-Ti, and K-Ti were prepared by treating the photocatalyst with a hot alkaline solution, in which the interparticle density of the Li-Ti sample was improved (see FIG. 3), and the sample and the K-Ti sample were confirmed to have particles that changed into a tubular shape and formed a fibrous tissue (see FIGS. 4 and 5).

[0084] In addition, according to the above-mentioned experimental results, the BET analysis confirmed that the specific surface area of ​​all three types of photocatalysts treated (modified) with high-temperature alkaline solution was increased compared to that of the photocatalyst before modification (4.6 times for the Li-Ti sample, 6.2 times for the Na-Ti sample, and 7.2 times for the K-Ti sample), the EXD analysis confirmed that the titanium oxide content was increased for all three types of photocatalysts modified with alkaline solution, and the XRD pattern confirmed that anatase crystals were formed in the photocatalyst calcined at 600°C. Also, the organic matter removal experiment confirmed that the modified and calcined photocatalysts exhibited excellent removal performance due to their improved activity and adsorption ability.

[0085] In addition, it was confirmed that the pre-treatment (modification) of the photocatalyst using alkaline materials gave good results, but the treatment process was complicated and may increase the production cost. To compensate for this, it was confirmed that pre-crystallized metatitanic acid (MTA) other than the crystallized photocatalyst (titanium oxide) can be modified by the modification method according to the present disclosure.

[0086] Metatitanic acid (MTA) may be modified by the photocatalyst modification method described above, i.e., ultrasonic dispersion of the photocatalyst in an alkaline solution such as sodium hydroxide (NaOH) or potassium hydroxide (KOH), followed by hydrothermal synthesis at a temperature of 100° C. to 130° C. for 15 to 20 hours to separate the photocatalyst into monolayers. In addition, metatitanic acid (MTA) may be calcined at a temperature of 300° C. to 550° C. (preferably 550° C.) to maximize activity and / or adsorption capacity.

[0087] In addition, as described above, the modification method according to the present disclosure may include a step of preparing a photocatalyst before the hydrothermal synthesis step, and the step of preparing a photocatalyst may include a step of preparing a photocatalyst powder. In the step of preparing a photocatalyst powder, the photocatalyst powder may be prepared using an acid-resistant medium. The effect of the step of preparing a photocatalyst powder in the modification method according to the present disclosure will be described later. The step of preparing a photocatalyst powder may be performed before the step of powdering the photocatalyst powder described above.

[0088] Additionally, the present disclosure provides a photocatalyst according to an embodiment of the present disclosure, which comprises a plurality of photocatalytic crystals modified by a photocatalytic modification method according to an embodiment of the present disclosure.

[0089] Additionally, the present disclosure provides a photocatalytic granular material (or granules) according to the first embodiment of the present disclosure. The photocatalytic granular material according to the first embodiment of the present disclosure includes a photocatalyst (modified photocatalyst) containing a plurality of photocatalytic crystals modified by a photocatalytic modification method.

[0090] Additionally, the photocatalyst comprising a plurality of modified photocatalytic crystals comprises a plurality of photocatalytic crystals modified by the photocatalytic modification method according to one embodiment of the present disclosure described above.

[0091] Additionally, the present disclosure provides a method for preparing a photocatalytic granular material according to an embodiment of the present disclosure. Hereinafter, a method for preparing a photocatalytic granular material according to a first embodiment of the present disclosure (hereinafter referred to as "the first photocatalytic granular material preparation method of the present disclosure") will be described. However, the first photocatalytic granular material preparation method of the present disclosure may use a photocatalyst modified by the photocatalytic modification method according to an embodiment of the present disclosure described above, and may include the photocatalytic modification method according to an embodiment of the present disclosure described above. Therefore, the redundant description of the photocatalytic modification method according to an embodiment of the present disclosure and the photocatalytic granular material according to the first embodiment of the present disclosure described above will be given briefly or omitted.

[0092] 14, the first preparation method of the present disclosure includes preparing a photocatalyst modified by the photocatalyst modification method according to one embodiment of the present disclosure described above (S100). The modified photocatalyst may include tubular crystals. Additionally, the tubular crystals may be formed by carrying out hydrothermal synthesis between photocatalyst powder and alkaline solution, isolating a monolayer, and then rolling the monolayer.

[0093] Additionally, referring to Fig. 14, the first preparation method includes a step of preparing a photocatalytic paste by mixing the modified photocatalyst and distilled water (S300). For example, the modified photocatalyst and distilled water may be mixed in a composition ratio of 75:25. Additionally, in step S300, a paste may be prepared by adding distilled water to the modified photocatalyst.

[0094] Additionally, referring to FIG. 14, the first preparation method includes a step of shaping (molding) the photocatalytic paste into a granular shape (S500). In step S500, the photocatalytic paste may be shaped into a granular shape by placing it in a pill maker. In step S500, the granules may be shaped by setting their size, taking into consideration the fact that the shaped granules will undergo drying shrinkage (e.g., the volume may be reduced by about 10%) during step S700 (drying step) described later. In other words, in step S500, the granules may be shaped to be larger than the photocatalytic granular material (photocatalytic granules after drying) to be finally adjusted, taking into consideration that the size of the granules will be reduced in step S700. Accordingly, the mold of the pill maker may be manufactured by taking into consideration that the size of the granular material will be reduced by about 10% after drying.

[0095] For reference, in this disclosure, granules (granular materials) may include various shapes, such as spheres (spherical), squares, triangles, pellets, and hexahedrons, etc. Accordingly, photocatalytic granular materials may be shaped into various shapes, such as spheres, squares, triangles, pellets, and hexahedrons.

[0096] Additionally, the molding conditions of the pill maker may be set so that the photocatalytic paste can be released from the mold and discharged in a granular shape.

[0097] Additionally, the compacted granules may contain moisture.

[0098] Additionally, referring to FIG. 14, the first preparation method includes a step of drying the molded granules to form a photocatalytic granular material (granules) (S700). In step S700, the moisture-containing bead (ring)-like granules formed in step S500 may be dried to be completely made into photocatalytic granules. At this time, the photocatalytic granules completely made by step S700 must have a certain hardness and powder should not be separated from the surface of the granules in order to be used for various purposes such as removing harmful substances (fine dust precursors, volatile organic compounds) and harmful microorganisms (viruses or bacteria). Step S700 may be performed to prepare such photocatalytic granules.

[0099] Additionally, in step S700, the granules may be dried using a drying oven. A non-continuous drying oven (batch oven) or a continuous drying oven (continuous oven) may be used as the drying oven. Non-continuous drying refers to a method in which the product is loaded and operated in cycles, i.e., the product remains inside the drying oven until the heat treatment is completed, while continuous drying refers to a method in which the heat treatment conditions of the product, such as temperature profile, oxygen concentration, etc., are set, and the product is moved directly and heat-treated according to the set conditions.

[0100] The heating conditions (performance conditions in step S700) according to the type of drying oven in the case of a continuous drying oven are shown in FIG. 15, and the heating conditions according to the type of drying oven in the case of a discontinuous drying oven are shown in FIG.

[0101] In addition, the present disclosure provides a photocatalytic granular material according to a second embodiment of the present disclosure (hereinafter referred to as "the second photocatalytic granular material of the present disclosure"). The second photocatalytic granular material of the present disclosure may be prepared by the photocatalytic granular material preparation method according to the first embodiment of the present disclosure described above. Therefore, redundant descriptions of the photocatalytic modification method according to an embodiment of the present disclosure, the photocatalytic granular material according to the first embodiment of the present disclosure, and the photocatalytic granular material preparation method according to the first embodiment of the present disclosure are given briefly or omitted.

[0102] In the second photocatalytic granular material of the present disclosure, the photocatalytic particles form tubular crystals.

[0103] The tubular crystals may be produced by isolating monolayers through photocatalysis and hydrothermal synthesis of alkaline solutions.

[0104] Hereinafter, a method for preparing a photocatalytic granular material according to a second embodiment of the present disclosure (hereinafter referred to as "the second preparation method of the present disclosure") will be described. However, in the description of the second preparation method of the present disclosure, redundant descriptions of the photocatalytic modification method according to one embodiment of the present disclosure, the photocatalytic granular material preparation method according to the first embodiment of the present disclosure, or the photocatalytic granular material according to the first and second embodiments of the present disclosure will be given briefly or omitted.

[0105] The second preparation method of the present disclosure can be applied to the molding of photocatalytic granules to ensure porosity.When the photocatalytic granules are porous, the decomposition / oxidation and adsorption capacity of gaseous harmful substances can be enhanced.

[0106] 17A and 17B, the second preparation method of the present disclosure includes preparing a photocatalyst modified by the photocatalyst modification method according to an embodiment of the present disclosure described above (S100). The modified photocatalyst may include tubular crystals. For example, in step S100, the photocatalyst powder and alkaline solution may be hydrothermally synthesized to separate a monoatomic layer, thereby pre-treating the crystals of the photocatalyst powder to have a tubular shape. For example, in step S100, the photocatalyst powder may be separated into a monoatomic layer by undergoing hydrothermal synthesis in an alkaline solution at a high temperature of at least 100° C. for a long time, and then the photocatalyst crystals may be converted into a tubular shape. Here, the alkaline solution may be sodium hydroxide (NaOH).

[0107] More specifically, in step S100, the photocatalyst having anatase phase may be dispersed in sodium hydroxide by ultrasonication, followed by hydrothermal synthesis at a temperature of 100°C to 130°C for 15 to 20 hours to react the photocatalyst, and then separated into a monolayer by centrifugation washing with HCl and distilled water. The separated monolayer may be rolled and converted into a tubular shape. Additionally, in step S100, drying or calcination may be performed to convert the monolayer into a tubular shape. This has been described in detail in the photocatalyst modification method described above, so the detailed description thereof will be omitted.

[0108] Additionally, referring to Figures 17A and 17B, the second preparation method of the present disclosure may include a step of producing a photocatalytic paste by mixing the modified photocatalyst and distilled water. In the step of producing a photocatalytic paste, the photocatalytic paste may be produced by additionally mixing an open-cell type circular foam made of a material having a melting point lower than that of the modified photocatalyst, or a piece of thread (a piece of thread) made of a material having a melting point lower than that of the modified photocatalyst. That is, the second preparation method of the present disclosure includes a step of mixing the modified photocatalytic powder and distilled water, and a step of producing a photocatalytic paste by additionally mixing an open-cell type circular foam made of a material having a melting point lower than that of the modified photocatalyst, or a piece of thread made of a material having a melting point lower than that of the modified photocatalyst (S300). For example, referring to Figure 17A, in step S300, a paste may be produced while adding the circular foam and distilled water to the modified photocatalytic powder. Alternatively, referring to Figure 17B, in step S300, a paste may be produced by adding a piece of thread and distilled water to the modified photocatalytic powder. Accordingly, in step S700 described later, the circular form or the piece of thread may be at least partially melted to form holes, and the photocatalytic granules may have porosity.

[0109] The circular foam may be made of a material containing at least one of polyethylene and polyurethane. However, the material forming the circular foam is not limited thereto, and a material having a lower melting point than that of the photocatalyst may form the circular foam. Additionally, the piece of thread may be made of a material containing at least one of polyethylene and polyurethane. However, the material forming the piece of thread is not limited thereto, and a material having a lower melting point compared to the photocatalyst may form the piece of thread.

[0110] For reference, FIG. 18 shows an example of an open cell type foam.

[0111] Additionally, referring to Figs. 17A and 17B, the second preparation method of the present disclosure includes a step of shaping (molding) the photocatalytic paste into a granular shape (S500). In step S500, the photocatalytic paste may be molded into a granular shape by placing it in a pill maker. In step S500, the granules may be molded by setting their size, taking into consideration the fact that the molded granules will undergo drying shrinkage (e.g., the volume may be reduced by about 10%) during step S700 (drying step) described later. In other words, in step S500, the granules may be molded to be larger than the photocatalytic granular material (photocatalytic granules after drying) that is finally adjusted, taking into consideration that the size of the granules will be reduced in step S700. Accordingly, the mold of the pill maker may be manufactured by taking into consideration that the size of the granular material will be reduced by about 10% after drying.

[0112] Additionally, the molding conditions of the pill maker may be set so that the photocatalytic paste can be released from the mold and discharged in a granular shape.

[0113] Additionally, the compacted granules may contain moisture.

[0114] Additionally, referring to FIGS. 17A and 17B, the second preparation method of the present disclosure includes drying the shaped granules to form photocatalytic granules (S700).

[0115] In step S700, the moisture-containing bead (ring)-like granules formed in step S300 may be dried to be completely prepared as photocatalytic granules. At this time, the photocatalytic granules completely prepared by step S700 must have a certain hardness and powder should not be separated from the surface of the granules in order to be used for various purposes such as removing harmful substances (fine dust precursors, volatile organic compounds) and harmful microorganisms (viruses or bacteria). Step S700 may be performed to prepare such photocatalytic granules.

[0116] Additionally, in step S700, the molded granules may be dried at a temperature higher than the melting point of the circular foam or the thread piece, so that at least a portion of the circular foam or the thread piece is melted. In other words, step S700 may be performed so that at least a portion of the circular foam is melted when the photocatalytic paste contains a circular foam. Additionally, step S700 may be performed so that at least a portion of the thread piece is melted when the photocatalytic paste contains a thread. Accordingly, the circular foam or the thread piece may be melted to form holes, and the photocatalytic granules may have porosity.

[0117] Additionally, in step S700, the granules may be dried using a drying oven. A non-continuous drying oven (batch oven) or a continuous drying oven (continuous oven) may be used as the drying oven. Non-continuous drying refers to a method in which the product is loaded and operated in cycles, i.e., the product remains inside the drying oven until the heat treatment is completed, while continuous drying refers to a method in which the heat treatment conditions of the product, such as temperature profile, oxygen concentration, etc., are set, and the product is moved directly and heat-treated according to the set conditions.

[0118] The heating conditions (performance conditions in step S700) according to the type of drying oven in the case of a continuous drying oven are shown in FIG. 19, and the heating conditions according to the type of drying oven in the case of a discontinuous drying oven are shown in FIG.

[0119] Additionally, the present disclosure provides a photocatalytic granular material according to a third embodiment of the present disclosure. The photocatalytic granular material according to the third embodiment of the present disclosure is prepared by the photocatalytic granular material preparation method according to the second embodiment of the present disclosure. The photocatalytic granular material according to the third embodiment of the present disclosure includes tubular crystals formed by the modified photocatalytic powder, and holes formed between at least a portion of the crystals. The holes are formed by drying granules prepared by molding a photocatalytic paste prepared by adding an open-cell type circular form made of a material having a melting point lower than that of the photocatalytic powder (modified photocatalytic powder) or a piece of thread made of a material having a melting point lower than that of the photocatalytic powder (modified photocatalytic powder) to the modified photocatalytic powder and distilled water at a temperature higher than the melting point of the circular form or piece of thread, so that the circular form or piece of thread is at least partially melted.

[0120] Additionally, tubular crystals may be produced by isolating monolayers through hydrothermal synthesis of photocatalysis and alkaline solutions.

[0121] Hereinafter, a method for preparing a photocatalytic granular material according to the third embodiment of the present disclosure (hereinafter referred to as "the third preparation method of the present disclosure") will be described. However, in the description of the third preparation method of the present disclosure, redundant descriptions of the photocatalytic granular material preparation method according to the first and second embodiments of the present disclosure or the photocatalytic granular material according to the first to third embodiments of the present disclosure will be given briefly or omitted.

[0122] 21, the third preparation method of the present disclosure includes coating granules with liquid photocatalyst at room temperature (S100). The granules are materials that do not contain photocatalyst. For example, the granules may be made of materials that contain at least one of ceramic, metal, glass, etc.

[0123] In step S100, the granules are immersed in the liquid photocatalyst or the liquid photocatalyst is sprayed onto the granules.

[0124] When the granules are coated with the liquid photocatalyst using a liquid immersion method in step S100, the granules to be coated, made of materials such as ceramic, metal, and glass, may be immersed in a container containing the liquid photocatalyst at room temperature, so that the liquid photocatalyst may be evenly distributed on the granules.

[0125] In addition, when the granules are coated with the liquid photocatalyst using a spraying method in step S100, the liquid photocatalyst may be applied by spraying at room temperature onto the material to be coated, such as ceramic, metal, or glass.

[0126] Additionally, referring to FIG. 21, the third preparation method of the present disclosure includes a step of forming photocatalytic granules by drying the granules coated with the liquid photocatalyst (S300). The photocatalytic granules completely formed by step S300 must have a certain hardness and the photocatalyst should not be separated from the surface of the granules in order to be used for various purposes such as removing harmful substances (fine dust precursors, volatile organic compounds) and harmful microorganisms (viruses or bacteria). Step S300 may be performed to prepare such photocatalytic granules. The liquid photocatalyst includes the photocatalyst modified by the modification method of the present disclosure described above.

[0127] Additionally, in step S300, the granules may be dried using a drying oven. A non-continuous drying oven (batch oven) or a continuous drying oven (continuous oven) may be used as the drying oven. Non-continuous drying refers to a method in which the product is loaded and operated in cycles, i.e., the product remains inside the drying oven until the heat treatment is completed, while continuous drying refers to a method in which the heat treatment conditions of the product, such as temperature profile, oxygen concentration, etc., are set, and the product is moved directly and heat-treated according to the set conditions.

[0128] The heating conditions (performance conditions in step S300) according to the type of drying oven in the case of a continuous drying oven are shown in FIG. 22, and the heating conditions according to the type of drying oven in the case of a discontinuous drying oven are shown in FIG.

[0129] Additionally, the present disclosure provides a photocatalytic granular material according to the fourth embodiment of the present disclosure. The photocatalytic granular material according to the fourth embodiment of the present disclosure is prepared by the photocatalytic granular material preparation method according to the third embodiment of the present disclosure.

[0130] This fourth photocatalytic granular material of the present disclosure includes granules. The granules may be made of a material containing at least one of ceramic, metal, glass, and the like.

[0131] Additionally, the fourth photocatalytic granular material of the present disclosure includes a photocatalytic coating layer formed on the surface of the granule and made of a photocatalyst. The photocatalytic coating layer is formed by immersing the granule in a liquid photocatalyst or spraying the liquid photocatalyst on the granule.

[0132] The photocatalyst and the photocatalytic granular material prepared by the photocatalytic granular material preparation methods according to the above first to fourth embodiments may have virus or bacteria removal properties.

[0133] Referring to Fig. 24, the photocatalyst before modification can remove 99% of bacteria, such as E. coli, Salmonella, etc., in 60 minutes. In addition, referring to Fig. 25 and Fig. 26, it can be confirmed that the photocatalyst before modification has a removal performance of 99% for various viruses, such as norovirus, rotavirus, bacteriophage MS2, human coronavirus (HcoV), etc., in 60 minutes. In other words, the photocatalyst can remove bacteria and viruses regardless of their type, and in particular, can continuously remove microorganisms that should be removed as time passes.

[0134] In addition, the virus removal performance of the three photocatalyst samples Li-Ti, Na-Ti, and K-Ti modified using the alkaline material according to the above modification method of the present disclosure as the photocatalyst constituting the granular material according to the present disclosure can be significantly improved compared to the photocatalyst before modification (control). In fact, referring to FIG. 27, it can be confirmed that the photocatalyst before modification exhibits a virus removal performance of 99.9% level in 30 minutes. In contrast, it can be confirmed that the three photocatalyst samples Li-Ti, Na-Ti, and K-Ti exhibit high removal performance of up to 99.9994% or higher (99.96% for Li-Ti, 99.997% for Na-Ti, and 99.9994% for K-Ti) in 30 minutes.

[0135] In addition, referring to Figures 28A, 28B, and 29, it can be confirmed that in the case of photocatalytic molded granules (more precisely, a non-filter type air purifying filter having multiple packaged photocatalytic granules), approximately 99% of influenza viruses are removed in 20 minutes.

[0136] In addition, the virus removal performance of the photocatalyst molded granules and the photocatalyst coated granules can exhibit remarkable anti-virus performance compared to a filter (ceramic filter) that is not coated with a photocatalyst. In fact, referring to Figures 30A, 30B, and 30C, it can be seen that the virus removal performance of the ceramic granules is the lowest, while the photocatalyst granules exhibit excellent virus removal performance of about 90% in 25 minutes.

[0137] Additionally, in the present disclosure, the photocatalyst or photocatalyst powder may contain titanium oxide. When the photocatalytic modification method according to one embodiment of the present disclosure described above is applied to titanium oxide, various impurities contained in titanium oxide crystals may be removed, and at the same time, tubular crystals may be formed, which may enhance the adsorption ability of the powder itself and bring about a synergistic effect of photocatalytic efficiency.

[0138] According to the photocatalytic modification method according to one embodiment of the present disclosure, the titanium oxide powder may be reacted in a high-temperature alkaline solution for a long time, and the titanium oxide powder may be separated into a monoatomic layer by the alkaline solution accordingly. The separated monoatomic layer may be rolled into a tube shape. In the process of decomposition by the alkaline solution, the impurities contained in the titanium oxide may be removed, and only the pure titanium oxide may be recovered. In addition, in the step of pretreating the photocatalytic powder (modification process), general titanium oxide may be added and mixed and stirred with the alkaline solution to carry out a reaction between them. At this time, the hydrothermal synthesis may be carried out while maintaining the temperature of the reactor at 130°C.

[0139] Also, for reference, as described above in this disclosure, the modification method may include a step of preparing a photocatalytic powder.

[0140] In the step of preparing the photocatalyst powder, the photocatalyst powder may be prepared using an acid-resistant medium. Referring to Fig. 31 and Fig. 32, the prepared photocatalyst powder may exhibit photocatalytic activity at a calcination temperature of 600°C or higher, but the photocatalytic activity may be significantly reduced after 700°C. In addition, the activity of the photocatalyst sample reprocessed at a calcination temperature of 640°C may be excellent.

[0141] For reference, FIG. 33 shows a TEM measurement photograph of the photocatalyst powder prepared by the steps of preparing the photocatalyst powder of the present disclosure, FIG. 34 shows the XRD measurement results of the photocatalyst powder prepared by the steps of preparing the photocatalyst powder of the present disclosure, FIG. 35 shows an SEM / EDX (X1,300) photograph of the photocatalyst powder prepared by the steps of preparing the photocatalyst powder of the present disclosure, and FIG. 36 shows an SEM / EDX (X10,000) photograph of the photocatalyst powder prepared by the steps of preparing the photocatalyst powder of the present disclosure.

[0142] The above description of the present disclosure is for illustrative purposes only, and it is understood by those skilled in the art that the present disclosure can be easily modified into other specific forms without changing the technical idea or essential features of the present disclosure. Therefore, the above-described embodiments should be understood as illustrative and not restrictive in all respects. For example, each component described as a singular form may be implemented in a distributed manner, and similarly, components described as being distributed may be implemented in a combined form.

[0143] The scope of the present disclosure is determined by the claims set forth below, rather than the above detailed description. All changes or modifications that come within the meaning and scope of the claims and their equivalents should be construed as being within the scope of the present disclosure.

Claims

1. 1. A photocatalytic modification method comprising: carrying out a hydrothermal synthesis to react the photocatalyst with an alkaline solution at a temperature of 100° C. or higher to separate a monolayer of the photocatalyst; and treating the hydrothermally synthesized photocatalyst so that the photocatalyst crystals have a tubular shape; The photocatalytic reforming method comprises:

2. The photocatalyst modification method according to claim 1, wherein the step of carrying out the hydrothermal synthesis is to react the photocatalyst at a temperature of 100°C to 130°C by mixing the photocatalyst with the alkaline solution.

3. The photocatalytic modification method according to claim 1 , wherein the alkaline solution contains at least one of Li, Na, and K.

4. The photocatalytic modification method according to claim 1 , wherein the photocatalyst has an anatase phase.

5. The photocatalyst modification method according to claim 1 , wherein the treating step comprises drying the hydrothermally synthesized photocatalyst.

6. The photocatalyst modification method according to claim 1 , wherein the treating step comprises calcining the hydrothermally synthesized photocatalyst.

7. The photocatalytic modification method according to claim 1, wherein the alkaline solution contains at least one of Na and K, and the photocatalyst has an anatase phase.

8. 8. The photocatalyst modification method according to claim 7, wherein the alkaline solution contains at least one of NaOH and KOH, and the step of carrying out the hydrothermal synthesis comprises dispersing the photocatalyst having the anatase phase in the alkaline solution by energy equivalent to ultrasound, and then carrying out the hydrothermal synthesis by reacting the photocatalyst with the alkaline solution at a temperature of 100°C to 130°C for 15 to 20 hours.

9. The photocatalytic modification method according to claim 1 , wherein the photocatalyst is titanium oxide or metatitanic acid.

10. A photocatalytic granular material comprising a photocatalyst having a plurality of photocatalytic crystals modified by the photocatalytic modification method according to any one of claims 1 to 9.

11. 1. A method for preparing a photocatalytic granular material, comprising: Preparing a photocatalyst modified by the photocatalyst modification method according to any one of claims 1 to 9; preparing a photocatalytic paste by mixing the modified photocatalyst with distilled water; forming the photocatalytic paste into granules; and drying the molded granules to form photocatalyst granules. A method for preparing a photocatalytic granular material comprising:

12. The photocatalytic granular material preparation method according to claim 11, wherein the step of producing the photocatalytic paste is further mixing an open-cell type circular foam made of a material having a melting point lower than that of the modified photocatalyst or a piece of thread made of a material having a melting point lower than that of the photocatalyst.

13. The photocatalytic granular material preparation method according to claim 12, wherein the step of drying the shaped granules is to dry the shaped granules at a temperature higher than the melting point of the circular foam or the piece of thread so that at least a portion of the circular foam or the piece of thread is melted.

14. The photocatalytic granular material preparation method according to claim 12, wherein the circular foam or the piece of thread is made of a material containing at least one of polyethylene and polyurethane.

15. 1. A method for preparing a photocatalytic granular material, comprising: Coating the granules with a liquid photocatalyst; and drying the granules coated with the liquid photocatalyst to form photocatalyst granules. Equipped with The coating of the granules with the liquid photocatalyst is performed by immersing the granules in the liquid photocatalyst or spraying the liquid photocatalyst onto the granules, the liquid photocatalyst containing the photocatalyst modified by the photocatalyst modification method according to any one of claims 1 to 9, and the granules being a material that does not contain the photocatalyst. Method for preparing photocatalytic granular material.

Citation Information

Patent Citations

  • Titanium oxide nano tube and preparing method thereof

    CN1528672A

  • Photocatalytic granular body, its function recovering method and apparatus for decomposing / Removing toxic organic matter by using the body and the method

    JP2003126702A

  • Porous photocatalyst

    JP2003170061A

  • Photocatalyst used for cleaning water quality

    JP2005254100A

  • Titania nanostructure and manufacturing method

    JP2015101504A